Law and language - Freeman, Michael D. A.; Smith, Fiona, LL. M. (Oxford : Oxford University Press, 2013)
'Law and Language' contains a broad range of essays by scholars interested in the interactions between law and language. This volume examines the themes of truth in language and the law, and the role of language in different areas of law, including contract and criminal law.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Law -- Language